Analogia Równań Coltriego i Guldana - Lisowski, A. (Engineering Transactions, 1961)
There are far reaching analogies between electric and chemical phenomena enabling many mechanical systems to be studied by means of electric layouts. The present paper is devoted to the application of electric network analogues to the solution of problems of bar structures. The considerations are based on Prof. MALECKI [4] and Soviet scientists, The Coltri potential equation for the solution of electric networks (2.2) are reduced to the same form as the equilibrium equations of nodes of the Guldan deformation method (1.16). This enables the simple determination of an electric analog for a mechanical system and the verification of the equilibrium equations of the nodes of a frame. Various support conditions are considered such as those of hinged, rigidly and elastically clamped support as well as the action of a moment acting on a node. As an example the node of Fig. 15 may be quoted. In the case of plane frames, fixed and moving nodes are considered. For the latter the two-stage procedure is used as usually with the Cross method. In the case of symmetric frames the advantages of applying symmetric and antisymmetric load are discussed. In conclusion, examples are given, in which the application of electric analog systems should prove more advantageous, than that of traditional computation methods. The solution for variable parameters (length, rigidity and number of bars) should be mentioned, enabling rational design of a structure, the determination of influence lines, the verification of computations, etc.